2013
DOI: 10.3389/fnsys.2013.00049
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm sensitivity in macaque monkeys

Abstract: This study provides evidence that monkeys are rhythm sensitive. We composed isochronous tone sequences consisting of repeating triplets of two short tones and one long tone which humans perceive as repeating triplets of two weak and one strong beat. This regular sequence was compared to an irregular sequence with the same number of randomly arranged short and long tones with no such beat structure. To search for indication of rhythm sensitivity we employed an oddball paradigm in which occasional duration devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…We did not find sensitivity to periodic structure in auditory cortex contacts, such as it was shown for the rat or macaque auditory cortex (37,38). Yaron et al (37) found neurons responding differently to fully predictable and unpredictable standards and deviants.…”
Section: Discussionmentioning
confidence: 83%
“…We did not find sensitivity to periodic structure in auditory cortex contacts, such as it was shown for the rat or macaque auditory cortex (37,38). Yaron et al (37) found neurons responding differently to fully predictable and unpredictable standards and deviants.…”
Section: Discussionmentioning
confidence: 83%
“…However, the authors found that the sensitivity for deviant detection is more developed in humans than monkeys. Humans detect deviants with high accuracy not only for the isochronous tone sequences but also in more complex sequences (with an additional sound with a different timbre), whereas monkeys do not show sensitivity to deviants under these conditions [62]. Overall, these findings suggest that monkeys have some capabilities for beat perception, particularly when the stimuli are isochronous, corroborating the hypothesis that the complex entrainment abilities of humans have evolved gradually across primates, and with a primordial beat-based mechanism already present in macaques [7].…”
Section: Functional Imaging Of Beat Perception and Entrainment In Humansmentioning
confidence: 99%
“…It has been hypothesised that an increase in precision is associated with an increase in subthreshold excitability of neural networks encoding the predicted stimulus (Prabhu et al ., ; van Elswijk et al ., ; Aggelopoulos, ), increasing the signal‐to‐noise ratio of neuronal responses to sensory stimuli. This hypothesis is compatible with the principles of active inference by which attention, by increasing the gain of sensory feedback, optimises precision (Brown et al ., ) and is consonant with the recent finding of an increase in the MEG field strength RMS by tone sequences of predictable patterns of tone frequencies (Barascud et al., ) and also agrees with our previous observation (Selezneva et al ., ) that neuronal responses to the long stimuli are enhanced in a temporally predictable sequence of stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…Previous observations on the effects of repeating patterns of stimuli on auditory stream formation made by us (Selezneva et al ., ) or others (Schroeder & Lakatos, ; Arnal & Giraud, ) have been made for periodic (isochronous) stimulus sequences and were explained by way of an entrainment of brain oscillations with the periodic stimulation. In this view, the oscillatory nature of up‐ and down‐regulation of neuronal activity (Castro‐Alamancos, ) has been considered to provide the prediction, or the internal forward model, about the timing of the upcoming stimuli, relative to which the auditory system computes the relationship with the stimulation at the predicted time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation